Expression of Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1α Increases After 8-Weeks of Endurance Training in Obese Females - Arya Dwi Prastickho; Desiana Merawati; Sugiharto Sugiharto (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aimed to prove the effect of moderate-intensity aerobic exercise on increasing Peroxisome proliferator-activated receptor-gamma coactivator-1alpha (PGC-1α) levels in obese women. A total of 12 women aged 20-25, with body mass index (BMI) of 25-30 kg/m2, normal systolic blood pressure, and normal resting heart rate as subjects in the study. Subjects were randomly divided into 2 groups, namely K1 (n=6; control without intervention) and K2 (n=6; aerobic exercise). The exercise was carried out with an intensity of 60% -70% HRmax, frequency 3x/week for 8 weeks. Pretest and posttest PGC-1α levels were analyzed using the Enzyme-linked immunosorbent assay (ELISA) method. The data analysis technique uses the Paired Sample T-Test with a significant level of 5%. Based on the results of the study it was concluded that aerobic exercise with an intensity of 60% -70% HRmax with a frequency of 3x/week for 8 weeks affected increasing PGC-1α levels in obese women.